BIAYA PRODUKSI KAYU LAPIS PADA BEBERAPA PERUSAHAAN DI SUMATRA SELATAN DAN KALIMANTAN SELATAN - Akub J Abdurachman; Sylviani Sylviani (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
A research in production cost and its distribution was conducted in several plywood manufacturers in South Sumatra and South Kalimantan. The average, distribution and variation of production cost are discussed in this report. The results showed that average cost of production was Rp 313,066 per cu.m. with coefficient of variation 9% consisting of average fixed cost Rp 59,135 per cu.m. with coefficient of variation 19% and average variable cost Rp 253,931 per cu.m. with coefficient of variation 12%. Average profit before taxes was Rp 78,827 per cu.m. or 26% of production cost with coefficient of variation 48%. Due to the fact that the largers component of the cost was used for material expense (56%) so it is advised the manufacturers should give more care the material processing aspect so that the waste could be reduced as small as possible.